The Impact of Knowledge Management in Human Resources Department: A Systematic Literature Review - Louis Dwysevrey Ompusunggu; Dana Indra Sensuse; Yolanda Yosephine Zebua (LPPM Universitas Duta Bangsa Surakarta, 2021)
The organization continually endeavors to create and improve the information on representatives associated with key business measures. It expects to make organization information in accomplishing upper hand. Inside an organization, the division that assumes the main part in obliging representatives' information needs is the Human Resource Department (HRD). Prior to building up information the board framework in an organization, particularly the Human Resources Department, it is important to direct a more inside and out investigation in regards to the effect that the organization has in the wake of executing the information the executive's framework, so partners can comprehend the effect that information the board has on an organization, particularly the HR Department. Subsequently, to control the HR Department to execute Knowledge Management, this precise writing survey (SLR) will try to address this inquiry: